Do banks practice what they preach? Brown lending and environmental disclosure in the euro area - Leonardo Gambacorta; Salvatore Polizzi; Alessio Reghezza; Enzo Scannella (European Central Bank (ECB), 2023)
This study examines whether the level of environmental disclosure in banks' financial reports matches less brown lending portfolios. Using granular credit register data and detailed information on firm-level greenhouse gas emission intensities, we find a negative relationship between environmental disclosure and brown lending. However, this effect is contingent on the tone of the financial report. Banks that express a negative tone, reflecting genuine concern and awareness of environmental risks, tend to lend less to more polluting firms. Conversely, banks that express a positive tone, indicating lower concern and awareness of environmental risks, tend to lend more to polluting firms. These findings highlight the importance of increasing awareness of environmental risks, so that banks perceive them as a critical and urgent pressing threat, leading to a genuine commitment to act as environmentally responsible lenders.
Keywords: G20; G21; M41; Q56; 330; green banking; brown lending; banking; environmental disclosure; environmental risks; climate change